Workplace bullying: Models of empirical estimation of the incidence and the psychological problems of victimization on a sample of employees in the Czech Republic - Cakirpaloglu, Panajotis; Smahaj, Jan; Cakirpaloglu, Simona Dobesova; Zielina, Martin; Slavíček, Ondřej (Psychologický ústav AV ČR, v.v.i., 2019)
Goals. The aim of the paper is to support the process of differentiation of the victims affected by bullying in the workplace as based on behavioral and subjective indicators of workplace as same as to examine the characteristics of the mental state of the bullied employees with the support of factual significance in individual subgroups. Sample and method. The survey sample consisted of 7,103 employees, aged 18-68 (26.26% men and 73.74% women, M = 42, SD = 11.03). The variables were recorded using the Czech version of the revised Negative Acts Questionnaire (NAQ-R) and the Structure and Dynamics of Subjective States (SUPSO) including the anamnestic questionnaire. Statistical analysis. Using the Statistica 12 program, the descriptive values, t-tests, including two vectors of the average values of the Hotelling test were carried out. The effect size (Cohen's d) were calculated using the formula from the basic numerical characteristics. Results. The results of the survey showed that bullying at the workplace is related with psychological well-being, activity, impulsiveness, tension, depression, anxiety and depression in the defined subgroups of bullied employees. Limitations. The major limitations of the study include the methodological limitations of the questionnaire. The questionnaire NAQ-R is also associated with limited comparability of the empirical findings concerning the prevalence of workplace bullying in different countries, due to the cultural, social, organizational and other specifics of the already realized studies. Also, choosing the local SUPSO method can open the question of comparability. The limit of research is also non-representativeness of selected sample of workers, as well as the unequal representation of men and women or the disparity between the state, non-profit and private sector.
Workplace bullying: Models of empirical estimation of the incidence and the psychological problems of victimization on a sample of employees in the Czech Republic
Keywords: workplace bullying; NAQ-R; SUPSO; rate of victimization awareness; effect size; combined assessing; workplace bullying; NAQ-R; SUPSO; rate of victimization awareness; effect size; combined assessing